2013
DOI: 10.1128/aac.00343-13
|View full text |Cite
|
Sign up to set email alerts
|

How Does Colistin-Induced Nephropathy Develop and Can It Be Treated?

Abstract: Colistin is an old antibiotic used in the treatment of Gram-negative infections. It was once suspended because of its nephrotoxic effect but has since been reintroduced due to multidrug-resistant bacterial infections. The pathogenesis of colistin-associated nephropathy has not been clarified, and there is currently no effective therapeutic or prophylactic agent available. The aim of this study was to investigate the roles of caspase-associated apoptosis and caspase 1, calpain 1, inducible nitric oxide synthase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 22 publications
5
80
0
1
Order By: Relevance
“…Lycopene has been shown to interact with ROS and thereby to prevent ROSinduced tissue and cellular damage (35). Consistent with previous studies, we revealed that colistin-induced nephrotoxicity is associated with significantly increased MDA levels and a concomitant decrease in the levels of antioxidant enzymes CAT, SOD, and GSH (Table 2) (16,18,60,61). In the present study, lycopene treatment restored the levels of all of these biomarkers to the normal range observed in the untreated control group (Table 2), confirming its nephroprotective effect.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Lycopene has been shown to interact with ROS and thereby to prevent ROSinduced tissue and cellular damage (35). Consistent with previous studies, we revealed that colistin-induced nephrotoxicity is associated with significantly increased MDA levels and a concomitant decrease in the levels of antioxidant enzymes CAT, SOD, and GSH (Table 2) (16,18,60,61). In the present study, lycopene treatment restored the levels of all of these biomarkers to the normal range observed in the untreated control group (Table 2), confirming its nephroprotective effect.…”
Section: Discussionsupporting
confidence: 92%
“…*, P Ͻ 0.05; **, P Ͻ 0.01 (compared to the control group); #, P Ͻ 0.05; ##, P Ͻ 0.01 (compared to the colistin group). [16][17][18]55). Increased production of ROS is an important mechanism in colistin-induced nephrotoxicity and neurotoxicity (17,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En la gran mayoría de los casos la falla renal aparece en los primeros siete días de tratamiento y la función renal se recupera tras la suspensión de éste, en al menos 90% de los casos 10 . El mecanismo específico de la nefropatía inducida por colistín no se conoce completamente, aunque modelos animales recientes sugieren que en su patogenia estarían involucrados el estrés oxidativo y la activación de algunas vías apoptóticas, como las caspasas 82 . La neurotoxicidad es otra de las preocupaciones de los clínicos al usar polimixina E, aunque su incidencia es mucho menor que el daño renal, es leve y además resuelve rápidamente tras la discontinuación del antimicrobiano 79 .…”
Section: Toxicidadunclassified